SOROPREVALÊNCIA E FATORES DE RISCO DA HEPATITE C EM DOADORES VOLUNTÁRIOS DE SANGUE NO HEMOCENTRO DE SÃO LUÍS MA - Fonseca, Lícia Maria Rodrigues (2006)
Introduction: Many carriers of HCV have been accidentally found on the occasion that they have donated blood. Despite rigorous triage during selection, several risk factors for HCV infection can still be identified in this population. Objective: (1) Determine prevalence of the HCV antibody in blood donors volunteer at the blood bank in São Luis (HEMOMAR). (2) Identify risk factors associated with this prevalence. Design: Case-control type study, with positive cases for HCV paired by sex and age in ratio of 1:1. Casuistic and Method: During the year 2004 there were 28,599 donors in the blood bank and 110 cases of anti-HCV positive. Twenty seven patients didn t come to the interview and were excluded from the study. The study was done with 83 cases and 83 controls. There was no difference with relation to age and sex among the 83 patients or the 27 who declined to take part. The differences between cases and controls were evaluated, in relation to risk factors already well-defined in literature, and in relation to more doubtful ones. The Chi Squared Test was used as was the Exact Fisher, when recommended. Logistical regression analysis identified independent factors associated with the presence of HCV. Results: The prevalence of HCV found during 2004 was 0.38%. The following variables presented association (P <0,010) with anti-HCV, in bivariant analysis: white colour (P=0.02), low level schooling (P=0.001), income less than two minimum salaries (P=0.001), lack of basic sanitation (P=0.08), use of illicit drugs (P= 0.06), blood transfusion (P=0.003) use of a razor while shaving (P=0.08) history of detention in penal facility (P=0.08). After adjusting the confusing factors in the multivariable logistic regression analysis, we were left with factors independently associated to positivity of anti-HCV; low income OR=5,041 (IC95%: 1.485 17,113; P<0.009), blood transfusion OR=12,100 (IC95%: 1.452 100,837; P= 0.02) and use of razor while shaving OR=2,687 (IC95%: 1,001 7,214; P= 0.04). Conclusion: This study permitted confirmation of a low prevalence of anti-HCV among blood donors. Among the factors independently associated with the presence of anti-HCV, low income stands out, which could mean little access to information on prevention of the disease. The use of a razor while shaving might constitute a way of transmitting the disease and measures should be taken to inform professionals who are involved with this activity.